Development of a Multiple Representation-Containing Students’ Worksheet Integrated with Problem-Based Learning to Improve Students’ Critical Thinking Skills on the Hydrocarbon Topic - Lutfiyani, Fiki Anisa; Nurhayati, Sri (Chemistry in Education, 2025)
The goal of this research study is to develop feasible and effective multiple representation-containing students’ worksheet integrated with Problem-Based Learning that receive feedback from students. This research uses the R&D method with the 4-D research model, which includes define, design, develop, and disseminate. The feasibility of the students’ worksheet is evident through the expert validators' assessment of the material and media experts' validation sheets, with average validation results of 88.59% and 90.41%, respectively, categorized as highly feasible. Additionally, a readability test was conducted, yielding a score of 88,33%, which is categorized as “very good”. Based on the expert validation and readability assessment results, the developed students’ worksheet is suitable for teaching hydrocarbon topic. The students’ worksheet effectiveness can be seen in the Wilcoxon test results, which were obtained from the students’ pretest and posttest scores to determine if there was significant improvement in their critical thinking skills. The Effect Size test yielded a value of 0,876, indicating high effectiveness. Based on these results, the students’ worksheet is effective in improving critical thinking skills. Students' responses yielded a percentage of 85.33%, categorized as "very interesting." The results showed that multiple representation-containing students’ worksheet integrated with Problem-Based Learning content improves Students’ Critical Thinking Skills on the Hydrocarbon topic.